Pengembangan Komik Digital sebagai Media Pembelajaran di SD Negeri 03 Gumawang - Lestari, Tri; Ni'am, Ahmad Ulin; Kholidin, Nor (Jurnal Riset Madrasah Ibtidaiyah, 2025)
Pancasila education requires innovative media to make it more engaging and easier for students to understand. Digital comics were chosen because they present the material visually and interactively. The product was developed using the research and development (R&D) based on the ADDIE model which includes analysis, design, development, implementation, and evaluation. Data were obtained through documentation and questionnaires, then analyzed from the aspects of media and material feasibility, as well as student and educator responses regarding practicality. The results of the study showed that digital comic media produced a very good level of validity, namely 95% from material experts and 88% from media experts. In the testing phase, student responses reached 85% in the limited group and 89% in the broader group. The assessment from educators showed a practicality level of 97% with the criteria of